Mapping the Water and Hygiene Research Landscape towards Sustainable Cities from 2012 to 2024: A Bibliometric Analysis - Fridayani, Helen Dian; Chiang, Li Chun; Widyasari, Sindy (Department of Government Studies, Universitas Syiah Kuala, 2025)
Sustainable water management remains a global challenge, especially in ensuring equitable access to clean water and sanitation. This research utilizes the PRISMA model and bibliometric analysis with VOSviewer to identify trends, major clusters, and gaps in the literature. The novelty of this study lies in the comprehensive bibliometric approach, which not only identifies research trends but also highlights critical gaps in policy effectiveness as well as public engagement in water and sanitation management. The results show that, despite various global efforts, governments are still unable to effectively address water management challenges, especially in ensuring equitable access to clean water and sanitation. In addition, the lack of public awareness of the environment is a significant obstacle. This research contributes to the existing literature by presenting a structured analysis of scholarly contributions, identifying key research clusters, and offering policy recommendations to bridge the gap between governance and community engagement in water sustainability efforts.